The effect of some environmental factors ondevelopment (Baghdad Science Journal, 2005)
That less duration takes larva mature into a virgin under field conditions is one day during Alguetrh from April to October and last longer to more than a day during Alguetrh from November to February and up to nine days in January when low minimum temperature to zero degreespercentage that these larvae can not be a high percentage in the field ranging from 90-100% reduced Hessian Alnsphaly 85% during the months of July and Cape